Effects of spa treatment on cardiac autonomic control at rest in healthy subjects - Corsini, Alessandro; Capogrosso, Michela; Perini, Renza (Sport sciences for health, 2015)
Purpose Heart rate variability (HRV) was analyzed after a spa-course to test the hypothesis that cardiac autonomic modulation can reflect the feeling of relaxation and well-being induced by the treatment. Methods Twenty healthy males were administered a spa-course, consisting in classic sauna (15 min), steam bath (10 min), and soft sauna (10 min), each of them followed by a cooling-off and a rest period. Heart rate (HR) and blood pressure (BP) were measured at rest in supine position before and after the treatment. HRV was analyzed in time and frequency domains and by Poincaré plot. Results After the treatment, systolic and diastolic BPs were decreased by about 13 and 6 mmHg, respectively ( p < 0.05 vs. before), while HR was unchanged (55 ± 7 b/min). HRV time domain and Poincaré parameters were significantly higher after than before the spa-course: SDNN, rMSSD, SD1 and SD2 increased by 31–35 %, NN50 and pNN50 by 64 %. The ratio SD1/SD2 was 0.6 ± 0.1 in both conditions. No modification was found in normalized power of spectral component and in their ratio (LF/HF = 1.3 ± 1.1, overall mean). Conclusions The increase in HRV with no change in markers of sympatho-vagal interaction observed after the spa-course would suggest an enhanced vagal modulation of HR, possibly reflecting the relaxing effect of the treatment. HRV analysis could be a useful tool to monitor changes in individual psychophysiological condition.